Surgery for massive malignant tumors of the left atrium – one center’s experience - Andrushchuk, Uladzimir; Ostrovsky, Youry; Zharkov, Vladimir; Amelchanka, Siarhei; Krutau, Valery; Yudina, Olga; Ilyina, Tatsiana; Grinchuk, Irina (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction: Surgery for primary non-resectable malignant tumors of the left atrium is controversial. Today heart autotransplantation as a method of surgical treatment for patients suffering primary massive malignant tumors of the left atrium is still not sufficiently studied. Material and methods: We provide information on our single-center 5-year experience in performing surgical interventions for massive malignant tumors of the left atrium and including cases of 5 patients (3 males – 60%, 2 females – 40%). One case (1/5, 20%) involved debulking surgery with partial resection of the left atrial (LA) wall and its reconstruction using a xenopericardium patch. Orthotopic heart transplantation was performed in 1 patient (1/5, 20%) and heart autotransplantation (HA) in the 3 other cases (3/5, 60%). Results: Mean myocardial ischemia duration was 165.6 ±12.0 minutes (range: 137–198), cardiopulmonary bypass (CPB) duration was 248.6 ±36.6 minutes (range: 188–392), and intervention duration was 498.0 ±77.4 minutes (range: 330–780). Mean total blood loss was estimated to be 2432 ±616.5 ml (range: 1610–4880). Major in-hospital complications were registered in 4 patients (4/5, 80%). In-hospital mortality was registered in 3 patients (3/5, 60%). Survival time in 2 (2/5, 40%) patients discharged from the hospital was 29 and 9 months, respectively. Both died because of disease progression. Conclusions: Surgery in patients with massive resectable primary malignant tumor of the left atrium is associated with high incidence of major hospital complications and mortality. Heart autotransplantation with radical tumor resection is the treatment of choice for these cases. The surgical approach implies thorough primary hemostasis and selection of a proper surgical approach, allowing revision of all the regions of intervention during each step. The possibility of excessive tension and bleeding in the area of bicaval anastomosis should be considered when performing heart autotransplantation, and appropriate preventive measures should be applied.